Beispiel Nr: 15
$ \text{Gegeben: } \\ P: y=a_1x^{2}+b_1x+c_1 \qquad g:y=mx+t\\ \text{Gesucht:Schnittpunkte zwischen Parabel und Gerade} \\ \text{Parabel-Gerade}\\ \textbf{Gegeben:} \\ p: y== x^2+4x+5 \qquad g: y==-2x-4 \\ \\ \textbf{Rechnung:} \\f\left(x\right)= x^2+4x+5\qquad g\left(x\right)=-2x-4\\ \bullet \text{Schnittpunkte zwischen zwei Funktionen} \\ f\left(x\right)=g\left(x\right) \\ x^2+4x+5=-2x-4 \\ x^2+4x+5-(-2x-4)=0\\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ 1x^{2}+6x+9 =0 \\ x_{1/2}=\displaystyle\frac{-6 \pm\sqrt{6^{2}-4\cdot 1 \cdot 9}}{2\cdot1} \\ x_{1/2}=\displaystyle \frac{-6 \pm\sqrt{0}}{2} \\ x_{1/2}=\displaystyle \frac{-6 \pm0}{2} \\ x_{1}=\displaystyle \frac{-6 +0}{2} \qquad x_{2}=\displaystyle \frac{-6 -0}{2} \\ x_{1}=-3 \qquad x_{2}=-3 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ \\ x^{2}+6x+9 =0 \\ x_{1/2}=\displaystyle -\frac{6}{2}\pm\sqrt{\left(\frac{6}{2}\right)^2- 9} \\ x_{1/2}=\displaystyle -3\pm\sqrt{0} \\ x_{1/2}=\displaystyle -3\pm0 \\ x_{1}=-3 \qquad x_{2}=-3 \end{array}\\ \end{array}\\ \\ \text{Schnittpunkt }1\\ f(-3)=2\\ S(-3/2)\\$